2D FPCB micromirror for scanning LIDAR. (1st December 2023) - Tai, Trevor S; He, Siyuan; Ghazinouri, Behrad
Abstract: This paper presents a 2D flexible printed circuit board (FPCB) micromirror and a scanning 3D light detection and ranging (LIDAR) based on it by integrating the 2D FPCB micromirror with a commercially available single point LIDAR. The 2D FPCB micromirror retains the benefits of previously developed 1D FPCB micromirrors, i.e. large aperture and low cost while providing rotation of the mirror plate about two orthogonal axes to be able to scan a laser beam about both vertical and horizontal axes to achieve 2D scanning. One 2D FPCB micromirror is integrated with a single point LIDAR to achieve a 3D scanning LIDAR, which, in comparison to the previously developed 1D FPCB micromirror based 3D LIDAR, achieved more compact structure and easier fabrication/assembly due to no strict requirement on the alignment between two micromirrors while only one 2D micromirror rather than two 1D micromirrors used. Prototypes of the 2D FPCB micromirror and the 3D LIDAR based on it are fabricated and tested. The test results demonstrate that the 2D FPCB micromirror based 3D LIDAR achieved a volume reduction over the previous 1D FPCB micromirror based 3D LIDAR from 1042 cm 3 to 754 cm 3 with a field of view of 40°× 24° at 150 Hz horizontal scanning and 2 Hz vertical scanning.